Peran BMT Darussalam dalam Memenuhi Kebutuhan Mahasiswa Universitas Islam Riau - Putri Nuraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The presence of BMT Darussalam is basically an idea to help ease the burden on students who need funds. The purpose of this study was to determine and analyze the role of BMT Darussalam in meeting the needs of students of the Faculty of Islamic Religion, Riau Islamic University. This research is a field research. The population in this study were students in the Faculty of Islamic Religion of Riau Islamic University who submitted funding for 2016 to 2018 totaling 88 people. The entire population was sampled using total sampling techniques. The data collection method is by observing, interviewing and distributing questionnaires. Data analysis is descriptive, data is grouped and described according to its type and analyzed using qualitative analysis, then presented in tabular form and supplemented with an explanation. The results of this study indicate that the existence of BMT Darussalam plays an active role in meeting the needs of students who need education funds in the form of financing programs, with a percentage of 87.69%. From the program BMT became a mediator between students who needed funding and the University. Furthermore, all the needs of students both in the form of academic funding needs, the need for financing academic facilities and financing needs for entrepreneurship can be met properly by BMT Darussalam by 88.18%. Keywords: Role, BMT Darussalam, Student Needs, UIR